Assessment of solid and liquid wastes management and health impacts along the failed sewerage systems in capital cities of African countries: case of Abidjan, Côte d'Ivoire - Ouattara, Zié Adama; Dongo, Kouassi; Akpoti, Komlavi; Kabo-Bah, Amos T.; Attiogbé, Francis; Siabi, Ebenezer Kwadwo; Iweh, Chu Donatus; Gogo, Guemegbo Hypolithe (Frontiers in Water, 2023)
The management of domestic wastewater and rain water is a major concern for the populations of Yopougon, especially the inhabitants of Yopougon ʺNouveau quartier". This article presents the causes of wastewater discharges from dysfunctional sewers and their health impact on the population and also highlights the environmental and health risks associated with poor solid and liquid waste management. This was based on literature search, semi-participatory workshop, physico-chemical and bacteriological characterization of wastewater and finally by a household survey. The field survey was conducted among 245 heads of households obtained using the Canadian statistical guidelines. The results obtained indicated that all main pollution indicators to be; total nitrogen (TN, 525±0.02 to 3077±0.3 mg/l), nitrates (NO3, 146±0.01 to 1347±0.12 mg/l), biochemical oxygen demand (BOD, 278±195.16 to 645±391. 74 mg/l), chemical oxygen demand (COD, 940±650.54 to 4050.5±71.42 mg/l) and total dissolved solids (TDS, 151±9.9 to 766±237.59 mg/l) were above the values recommended by the World Health Organization (WHO) and Cote d’Ivoire national policy guidelines standards for the discharge of effluents into the environment. The analysis of the bacterial flora of the effluents revealed that the concentrations of fecal coliforms and fecal streptococci exceeded the values recommended by the WHO and national policy guidelines standards. Under these conditions, the populations of this area are bound to be faced with infectious diseases. Diseases such as malaria (84.53%), respiratory infections (61%), diarrhea (48.66%), intestinal diseases (44.5%) and typhoid fever (28.84%) were prevalent in the surveyed households.